The end of alchemy money, banking, and the future of the global economy - King, Mervyn A. (New York W. W. Norton & Company, 2016)
The past twenty years saw unprecedented growth and stability followed by the worst financial crisis the industrialised world has ever witnessed. In the space of little more than a year what had been seen as the age of wisdom was viewed as the age of foolishness. Almost overnight, belief turned into incredulity.
Includes bibliographical references (pages 371-417) and index.
Keywords: Capitalism